2007
DOI: 10.1111/j.1468-1331.2007.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of adverse events most commonly associated with topiramate for migraine prevention

Abstract: The efficacy, safety and tolerability of topiramate has been demonstrated in three large multicenter, randomized, double-blind, placebo-controlled trials. To characterize the time course of adverse events (AEs) that led to treatment discontinuation in >/=2% of patients who received topiramate 100 mg/day during three pivotal, multicenter, randomized, double-blind, placebo-controlled, and 26-week trials. The pooled population comprised all randomized patients who reported safety data during the double-blind phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
2
44
0
7
Order By: Relevance
“…16,17 Preventive treatments aim to reduce headache frequency by at least 50 % 18-20 without intolerable harms. 21,22 In clinical practice, physicians and patients choose preventive treatments based primarily on FDA approval and drug tolerability. 9,18,19,[23][24][25] Systematic reviews and meta-analyses with consistent and transparent appraisal of study quality and strength of evidence are essential for arriving at evidence-based migraine preventive treatment and policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Preventive treatments aim to reduce headache frequency by at least 50 % 18-20 without intolerable harms. 21,22 In clinical practice, physicians and patients choose preventive treatments based primarily on FDA approval and drug tolerability. 9,18,19,[23][24][25] Systematic reviews and meta-analyses with consistent and transparent appraisal of study quality and strength of evidence are essential for arriving at evidence-based migraine preventive treatment and policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs proved equally effective in improving several pain/disability parameters, but the safety profile was higher for onabotulinumtoxinA and the discontinuation rate significantly higher for topiramate [adverse events (AEs) being the major reason for withdrawal] (discontinuation rates 25-44.2 % for topiramate; 10-25 % for onabotulinumtoxinA) [12,[65][66][67][68][69].…”
Section: Re-prophylaxismentioning
confidence: 98%
“…Lainez et al [36] analyzed three large multicentre studies, and found that therapy discontinuation occurred in 25% of patients administered Topiramate and in 1% of patients treated with placebo. The most common adverse events were paresthesias (8.0%), cognitive symptoms (7.3%), fatigue (4.7%), insomnia (3.4%), nausea (2.3%), loss of appetite, anxiety, and dizziness (2.1%).…”
Section: Topiramatementioning
confidence: 98%